2017
DOI: 10.3855/jidc.8241
|View full text |Cite
|
Sign up to set email alerts
|

Emerging fluoroquinolone and ketolide resistance in Haemophilus parainfluenzae in South Africa

Abstract: This item has no abstract. Follow the links on the page to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Interestingly, for the isolates with a Ͼ4-fold increase in fluoroquinolone MIC values from both arms, 3 out of the 4 isolates were genetically unrelated. Previous studies from Spain and South Africa reported fluoroquinolone resistance arising from mutations in the QRDR as well as plasmid-mediated resistance (9,10). The mutations observed in H. parainfluenzae in this study were also observed in isolates reported in the Spanish and South African studies.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, for the isolates with a Ͼ4-fold increase in fluoroquinolone MIC values from both arms, 3 out of the 4 isolates were genetically unrelated. Previous studies from Spain and South Africa reported fluoroquinolone resistance arising from mutations in the QRDR as well as plasmid-mediated resistance (9,10). The mutations observed in H. parainfluenzae in this study were also observed in isolates reported in the Spanish and South African studies.…”
Section: Discussionsupporting
confidence: 75%
“…Levels of Haemophilus parainfluenzae , a commensal organism, were significantly higher in post‐treatment samples than in healthy sites, a finding also observed in chronic periodontitis volunteers treated with adjunctive MTZ and AMX 47 . This may be in part due to a transition to a healthy microbiome but also because this species is often resistant to β‐lactam antibiotics 48 . The same may be argued for Corynebacterium, especially C. durum , which was strikingly elevated post‐treatment to an abundance slightly higher than that observed in healthy samples.…”
Section: Discussionmentioning
confidence: 66%
“…The ErmB gene which codes for methylases has also been implicated in macrolide, azalide and ketolide resistance by H. parainfluenzae. 18 Substitutions in the L22 ribosomal protein and in the 23S rRNA have not yet been reported in macrolide resistant H. parainfluenzae. 15 However, the involvement of other resistance mechanisms of the bacteria to macrolides is still to be determined.…”
Section: Macrolides Azalides Ketolides Lincosamides and Streptograminsmentioning
confidence: 99%
“…Of the studies that investigated the involvement of plasmid mediated resistance genes (qnrA, qnrB, qnrS, qnrC, qnrD, qnrVC, qepA and aac(6′)-Ib-cr genes), 15,17,19,20,34 only one detected aac(6′)-Ib-cr in four isolates of H. parainfluenzae. 18…”
Section: Quinolonesmentioning
confidence: 99%